Manufacturing Technologies : Materials, Operation and Applications : Special topic volume with invited peer reviewed papes only - Krenicky, Tibor, editor; editor (Zurich, Switzerland : Trans Tech Publications Ltd, 2017)
Includes bibliographical references and indexes